Keterampilan Interpersonal dalam Negoisasi - Ramadani, Mutiara Rahayu Oktri; Robain, Wilchan; Ramadhani, Nabila Suci; Surbakti, Farhan Yananda; Deska, Fifi; Novita, Nazwa (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
Negotiation is a strategic communication process in which multiple parties work to reconcile differences and reach mutually beneficial agreements through the exchange of information, interests, and viewpoints. Although traditional theories emphasize analytical elements such as developing a BATNA, crafting offer–counteroffer strategies, and employing persuasive framing, recent research underscores the growing importance of interpersonal competencies in shaping negotiation success. Through a qualitative literature-based approach, this study explores how empathy, assertive communication, and emotional regulation influence negotiation outcomes, examines their relevance in digital negotiation environments, and proposes an integrated training framework for professionals and entrepreneurs. The findings reveal that empathy strengthens a negotiator’s ability to interpret emotional cues, identify underlying concerns, and build trust, thereby minimizing miscommunication. Assertive communication supports clear expression of interests and boundaries while maintaining respect, which enhances collaborative problem-solving. Emotional regulation promotes composure and cognitive flexibility, particularly in high-pressure interactions. In technology-mediated negotiations conducted via email, messaging platforms, or virtual meetings, these skills must be adapted due to limited physical cues and higher risk of misinterpretation, requiring explicit wording and intentional emotional management. The proposed model incorporates empathy training, assertive communication development, emotional regulation practices, and digital negotiation skills to cultivate adaptive and emotionally intelligent negotiators.